Developing Students’ Character through Integrated Anti-Corruption Education - Baharuddin Baharuddin; Ita Sarmita Samad (Universitas Muhammadiyah Enrekang, 2019)
Corruption has become an acute problem for the Indonesian people since independence. Various efforts have been made to hack the corruption problem but have not succeeded. The cultural approach would be a solution to the problem. The cultural approach in question is education. Through education, prevention of corruption can be done by creating a healthy environment, strengthening character, and internalizing the noble values ​​in daily behavior for students. Strengthening of character is reflected by cultivating shame, socialization about the importance of honest culture and the bad of cheating both directly and indirectly. Termsuk by making the